What type of monetary and exchange rate cooperation do China's Asian neighbors want from China? - Maria Socorro Gochoco-Bautista; Raul V. Fabella (University of the Philippines, School of Economics (UPSE), 2006)
It is generally taken for granted that China's monetary and exchange rate policy have repercussions on her Asian neighbors and affect the choice set open to them in terms of setting optimal economic policy. At the very least, China's neighbors would like to have a clearer idea of China's plan as regards her monetary and exchange rate policy, specifically how and in what time frame she intends to adjust or exit from the current dollar peg. In a broad sense, China's decision regarding what some might call 'national monetarism' will affect the viability of 'international monetarism,' or the regional or global monetary and exchange rate arrangement, with the yuan playing a key role. Already, many countries in Asia have individually opted to adopt inflation targeting and more flexible exchange rate regimes following the Asian Crisis of 1997. One may question whether indeed adopting inflation targeting cum greater exchange rate flexibility is optimal in the light of current China policy and relative to adopting a regional monetary standard. From China's perspective, the choice of an optimal monetary and exchange rate strategy is largely contingent on the goals of policymakers there and what they consider to be in China's best interests. From the perspective of China's neighbors in Asia, however, the effects of China's decisions on her monetary and exchange rate policy are likely to have uneven trade and exchange rate effects in the different Asian countries. The differing degrees of complementarity between individual Asian countries and China will give rise to differences in the direction and size of exchange rate adjustment in individual countries. This, in turn, implies that a regional monetary arrangement to address intra-regional fluctuations in response to a change in China's monetary and exchange rate arrangement may not be warranted. The study will try to assess to what extent such a view is valid for some countries in Asia.
Keywords: 330; Geldpolitik; Wechselkurspolitik; Internationale Zusammenarbeit; China; Asien